How National Culture Influences the Speed of COVID-19 Spread: Three Cross-Cultural Studies. (April 2023) - Huang, Xiaoyu; Gupta, Vipin; Feng, Cailing; Yang, Fu; Zhang, Lihua; Zheng, Jiaming; Van Wart, Montgomery
The COVID-19 pandemic has affected 222 countries and territories around the globe. Notably, the speed of COVID-19 spread varies significantly across countries. This cross-cultural research proposes and empirically examines how national culture influences the speed of COVID-19 spread in three studies. Study 1 examines the effects of Hofstede's national cultural dimensions on the speed of COVID-19 spread in 60 countries. Drawing on the GLOBE study (House et al., 2004 ), Study 2 investigates how GLOBE cultural dimensions relate to the speed of the pandemic's spread in 55 countries. Study 3 examines the effect of cultural tightness in 31 countries. We find that five national cultural dimensions – power distance, uncertainty avoidance, humane orientation, in-group collectivism, and cultural tightness – are significantly related to the speed of COVID-19 spread in the initial stages, but not in the later stages, of the pandemic. Study 1 shows that the coronavirus spreads faster in countries with small power distance and strong uncertainty avoidance. Study 2 supports these findings and further reveals that countries with low humane orientation and high in-group collectivism report a faster spread of the disease. Lastly, Study 3 shows that COVID-19 spreads slower in countries with high cultural tightness.